1994
DOI: 10.1111/j.1476-5381.1994.tb14861.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duration of ischaemia on reduction of myocardial infarct size by inhibition of neutrophil accumulation using an anti‐CD18 monoclonal antibody

Abstract: Neutrophil accumulation is a characteristic feature of the inflammatory response in myocardial tissue which has undergone a period of ischaemia. The aim of this study was to examine whether inhibition of myocardial neutrophil infiltration, using an antibody to the CD18 leukocyte adhesion molecule, was effective in reducing infarct size in anaesthetized rabbits. Anaesthetized rabbits underwent coronary artery occlusion (CAO) for periods of 30 or 45 min followed by reperfusion for 3 h. Animals were treated intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In rabbits with myocardial infarction, anti-CD18 therapy was effective after coronary occlusion lasting 30 but not 45 minutes. 18 By contrast, in dogs with neutrophil depletion, myocardial necrosis was reduced with ischemia of either 90 or 240 minutes. 5 Sharar et al 3 found, using a rabbit ear preparation and 6 hours of occlusion, that administration of anti-CD18 therapy immediately on reperfusion was as effective as that initiated 1 hour but not 4 hours later.…”
Section: Discussionmentioning
confidence: 89%
“…In rabbits with myocardial infarction, anti-CD18 therapy was effective after coronary occlusion lasting 30 but not 45 minutes. 18 By contrast, in dogs with neutrophil depletion, myocardial necrosis was reduced with ischemia of either 90 or 240 minutes. 5 Sharar et al 3 found, using a rabbit ear preparation and 6 hours of occlusion, that administration of anti-CD18 therapy immediately on reperfusion was as effective as that initiated 1 hour but not 4 hours later.…”
Section: Discussionmentioning
confidence: 89%
“…Myeloperoxidase (MPO) activity was measured as described previously (8). The frozen NZ and AR samples were homogenized in 0.02 M NaPO4 buffer (pH 4.7) containing 0.1 M NaCl and 0.015 M Na2 EDTA, and centrifuged at 20,000 g for 15 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil accumulation is markedly accelerated during reperfusion (3,4) and early studies implicated this cell in the associated tissue damage. Thus, systemic neutrophil-depletion (5) and antibodies blocking leukocyte adhesion molecules have been shown to limit infarction (6)(7)(8). This link between neutrophils and damage is controversial, as it has been reported in some models that agents affecting neutrophils do not influence infarction (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple additional factors contribute to cell death as the infarcted area expands and more border cells die. These include collateral damage from necrosis and infiltrating macrophages (Williams et al, 1994), additional necrotic and apoptotic death resulting from energy (glucose and ATP) depletion (Buja et al, 1993;Hochachka et al, 1996;Majno and Joris, 1995;Reimer and Ideker, 1987;Mani and Kitsis, 2003), and changes associated with hypoxia. The pathways of ischemic injury are the subjects of intensive study because descriptions of these pathways may lead to new methods of reducing tissue loss and minimizing the damage caused by infarction and heart attack.…”
mentioning
confidence: 99%